Eksplorasi Faktor-Faktor Green Purchase Intention Pada Pengguna Potensial Kendaraan Listrik - Erik, Erik; Maulana, Herdiyan; Widyastuti , Liza Yudhita (Jurnal sosial dan sains, 2025)
This study aims to identify the factors influencing the purchase intention of environmentally friendly products, specifically electric motorcycles, among potential users. The research adopts a quantitative approach. The sample consists of 532 respondents who are considered potential users of electric motorcycles. The instruments used include: Attitude towards green products (adapted from McCarty and Shrum, 1994), Subjective norms and perceived behavioral control (adapted from Armitage and Conner, 1999), Green purchase intention (adapted from Chang and Chen, 2008), Collectivism (adapted from Sharma, 2010), Ecological knowledge (adapted from Akbar et al., 2014). Data analysis used Pearson correlation to examine relationships between variables and hierarchical regression to test two models. The results indicate that attitude towards green products, subjective norms, perceived behavioral control, ecological knowledge, and collectivism are significantly related to green purchase intention. The first hierarchical regression model revealed that these variables collectively explain 32.2% of the variance in green purchase intention. The second model, which incorporates collectivism and ecological knowledge, exhibits an increase in explanatory power, with an R-squared change of 0.035, or 3.5%. The study implies that enhancing collectivism and ecological knowledge can increase potential electric motorcycle users' intentions to adopt such vehicles. Therefore, it is recommended that the government provide collective education about electric motorcycles and enhance ecological knowledge among potential users in the community.